Exploratory Review of Disaster Risk Assessment Models for Promoting Effective Disaster Risk Reduction in Pakistan - Quratul Ain, Anwar (2018)
The national and international focus has been directed towards risk reduction due to the immense impact of a disaster and the aftermath that requires the expenditure of resources for repairs of the damages caused by these disasters. The continued evolution of risks has increased the need for effective disaster risk assessment in order to provide information to disaster risk management planning and disaster risk reduction intervention process. An approach towards disaster risk assessment that is organized and systematic will aid in the maintenance of the credibility, therefore, promoting quality of the process and its results. Specific models designed for the task acts as an essential tool for the methodological approach towards disaster risk assessment. Due to lacking a proper model for disaster risk assessment, the local government of Pakistan has taken under consideration the need for this study and therefore has expressed the need for an integrated and holistic disaster risk assessment model. In the process of developing an effective disaster risk assessment model, the research was led in direction of establishing a preliminary link between disaster risk assessment and disaster risk reduction in order to determine the key factors in effective disaster risk reduction. The preliminary analysis involved in formulating a theoretical hypothesis of disaster risk assessment examined the key factors informing the disaster risk assessment process. This debate continued to compare and review three disaster risk assessment models the Community-wide Vulnerability Capacity Assessment (CVCA) Model, the Community-Based Risk Reduction Model and the South African Disaster Risk Assessment Model analyzing key characteristics, infrastructure and implications of the models. The reviewing comparison of the three highlighted models provided the necessary insight needed for developing disaster risk assessment model for the local government in Pakistan Municipalities. The final development of disaster risk assessment for the local government in Pakistan was credited to these researchers and findings that were the subjective guidelines.